Hubungan Kontrol Diri Dengan Tindakan Agresivitas Penggunaan Media Sosial Pada Remaja Di SMA Negeri 12 Kota Batam - Adhyatma, Aminah Aatinaa; Fariningsih, Erika; Aditya, Aditya (NHM PRESS, 2023)
Background : In 2022, almost 89.15% of the population in Indonesia is connected to the Internet. The use of social media is highest among adolescents aged 13 - 18 years, but social media does not only have a positive impact but there are negative impacts, especially in the form of verbal aggressiveness. Method : This type of research is quantitative research with a cross sectional approach, samples were taken using simple random sampling. The measuring instrument uses a questionnaire that has been tested for validity and reliability. Data analysis using Spearman Rank's test Result : The results describe from 75 respondents, about 16% of adolescents have a high level of self-control, 50.7% have a sufficient level of self-control, and 33.3% have a low level of self-control and about 30.7% of adolescents show positive aggressive behavior in using social media, while 69.3% show negative aggressive behavior. Statistical analysis shows that there is a significant relationship between level of self-control and aggressive behavior in using social media among adolescents in SMA Negeri 12 Batam City.